2006
DOI: 10.1111/j.1468-1293.2006.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nevirapine‐switch strategies for HIV treatment

Abstract: Despite the benefits of protease inhibitor (PI)-based HIV treatment, issues of tolerability, dosing frequency, pill count and long-term metabolic complications necessitate evaluation of alternate treatment strategies. The weight of evidence demonstrates that a switch from a PI-based regimen to one containing nevirapine can be accomplished safely while maintaining virological suppression. There is no immunological cost. There is probably an overall benefit in terms of the metabolic milieu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It should also be noted that patients who are virologically suppressed on a boosted PI regimen can be safely switched to an NVP-based regimen, with no apparent adverse immunologic effects and with potential benefits to the patient's metabolic profile. 26 Another important consideration, especially for patients with a history of depression or mental illness, is that NVP treatment was associated with the resolution of EFV-associated neuropsychiatric events in patients switched to an NVP-based regimen. 27 Clinical trials with the XR formulation in treatment-naive and treatment-experienced patients have demonstrated that the virologic efficacy and safety of the recently approved XR formulation (NVP XR) is comparable with the original IR formulation (NVP IR).…”
Section: Durability Of Virologic Suppressionmentioning
confidence: 99%
“…It should also be noted that patients who are virologically suppressed on a boosted PI regimen can be safely switched to an NVP-based regimen, with no apparent adverse immunologic effects and with potential benefits to the patient's metabolic profile. 26 Another important consideration, especially for patients with a history of depression or mental illness, is that NVP treatment was associated with the resolution of EFV-associated neuropsychiatric events in patients switched to an NVP-based regimen. 27 Clinical trials with the XR formulation in treatment-naive and treatment-experienced patients have demonstrated that the virologic efficacy and safety of the recently approved XR formulation (NVP XR) is comparable with the original IR formulation (NVP IR).…”
Section: Durability Of Virologic Suppressionmentioning
confidence: 99%
“…It is important to note that after the initial 16 weeks of treatment, the incidence of adverse liver events is similar between nevirapine and efavirenz [74]. Studies in which stable protease inhibitor-based regimens are switched to nevirapine have suggested that the 'nevirapine hypersensitivity syndrome' can be avoided by the utilization of nevirapine switch strategies [75][76][77].…”
Section: Antiretroviral-related Liver Toxicitymentioning
confidence: 99%
“…This is probably a combination of physicians and patients being reluctant to switch treatment once vir-ological control has been achieved; however, several switch studies now show that, in general, virological efficacy is maintained after switching. 16,17 More frequent monitoring is also a concern when a patient switches to a new agent, but most patients can usually find time for the few additional visits that may be required following a change in therapy. New side-effects or exacerbation of current side-effects are always a possibility when starting new drugs, but careful counselling, preparation and management of side-effects will help.…”
Section: Current Evidencementioning
confidence: 99%